Optimalisasi Reels Instagram Sebagai Media Promosi: Studi Kasus UMKM Salon Eyelashtika Kota Malang - Farika, Siti; Rochman, Fatkhur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Salon Eyelashtika Kota Malang is an SME in the beauty industry that focuses on nail art and eyelash extension services. Its promotions are still limited to WhatsApp and Instagram, with content consisting of photos without videos, which does not have a significant impact on increasing engagement. Therefore, this study aims to create video advertising content that is broadcast through the Instagram Reels feature to increase the effectiveness of Salon Eyelashtika's promotions. This study used the Action Research method, which consists of four stages: planning, action, observation, and reflection. Video content was created using Sony Vegas Pro 14.0 software. Effectiveness was assessed through the distribution of questionnaires based on the EPIC (Empathy, Persuasion, Impact, Communication) model to two management experts, two computer experts, and 20 prospective customers. The analysis results showed an EPIC rate of 4.6, which falls into the highly effective category, as well as a 5.2% increase in Instagram engagement rate after the video was published. These results prove that video ad content can capture audience attention and increase interaction on social media. The Instagram Reels video ad created was proven effective in increasing the engagement of the Salon Eyelashtika Instagram account. This strategy is recommended for SMEs to enhance visibility and promotional appeal through suitable digital platforms.